Metabolic Control of Brain Homeostasis - Susan A. Masino (Frontiers Research Topics, 2017)
Brain function is under metabolic control, which in turn determines the equilibrium of homeostatic systems that affect neuronal and glial networks on the molecular, cellular, and systems levels. The collection of articles ranges from molecules and mechanisms involved in regulating homeostasis and neuronal excitability to therapeutic mechanisms tailored to restore homeostatic function. It also features neurological diseases and novel treatment approaches that are based on metabolic and homeostatic interventions. Together, the collection of articles outlines novel strategies to restore brain function in neurology and highlights limitations of conventional pharmacological approaches. We suggest that restoration of molecular and biochemical networks could lead to a new era of therapeutic opportunities.